2023
DOI: 10.3390/electronics12071535
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Method for Sugarcane Syrup Brix Based on Improved Support Vector Regression

Abstract: The brix of syrup is an important parameter in sugar production. To accurately measure syrup brix, a novel measurement method based on support vector regression (SVR) is presented. With the resonant frequency and quality factor as inputs and syrup brix as the output, a mathematical model of the relationship between the resonant frequency, quality factor, and syrup brix is established. Simultaneously, the particle swarm optimization (PSO) algorithm is used to optimize the penalty coefficient and radial basis ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…SVR is a machine learning method that is used to solve regression problems [20]. It seeks a hyperplane to fit data by mapping the original data onto a high-dimensional characteristic space, aiming to minimize the distance from the data points to the hyperplane [21].…”
Section: Svr Modelmentioning
confidence: 99%
“…SVR is a machine learning method that is used to solve regression problems [20]. It seeks a hyperplane to fit data by mapping the original data onto a high-dimensional characteristic space, aiming to minimize the distance from the data points to the hyperplane [21].…”
Section: Svr Modelmentioning
confidence: 99%
“…The results showed that the new model applied to the long-term compensation of pressure sensors affected by measured drift. Hu et al [23] used the penalty coefficient and radial basis kernel function of the particle swarm optimization algorithm SVR for optimization. By measuring the actual samples, it was proved that the optimized calculation model had better prediction performance.…”
Section: Introduction 1backgroundmentioning
confidence: 99%